#### Answer

y=$x^{2}-\frac{5}{3}x^{3}$+C

#### Work Step by Step

dy=$(2x-5x^{2})$dx
$\int$dy=$\int$$(2x-5x^{2})$dx
y=$x^{2}-\frac{5}{3}x^{3}$+C

Published by
Brooks Cole

ISBN 10:
1-28505-709-0

ISBN 13:
978-1-28505-709-5

y=$x^{2}-\frac{5}{3}x^{3}$+C

dy=$(2x-5x^{2})$dx
$\int$dy=$\int$$(2x-5x^{2})$dx
y=$x^{2}-\frac{5}{3}x^{3}$+C

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.